2006
DOI: 10.1093/carcin/bgl209
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in aberrant crypt foci from patients without concurrent colon cancer

Abstract: Aberrant crypt foci (ACF) are microscopic surface abnormalities that are putative precursors to colorectal cancer (CRC). ACF exhibit similar histological and molecular abnormalities to adenomas and CRC and potentially represent useful biomarkers of cancer risk. Microsatellite instability (MSI) is one molecular abnormality identified in concurrent ACF from CRC patients that may indicate a risk for progression. To determine if MSI can be detected in ACF from cancer-free subjects, we examined 45 ACF from 20 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…ACF were visualized and photographed using an Olympus close-focus colonoscope (XCF-Q160ALE; Olympus Corp., Center Valley, PA) that by employing a focal length of 2 to 100 mm permits high magnification (Â60) to be sustained over a longer visualizing distance. This allows for an increased ACF retrieval rate on biopsy (12,13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACF were visualized and photographed using an Olympus close-focus colonoscope (XCF-Q160ALE; Olympus Corp., Center Valley, PA) that by employing a focal length of 2 to 100 mm permits high magnification (Â60) to be sustained over a longer visualizing distance. This allows for an increased ACF retrieval rate on biopsy (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…Frozen serial sections of ACF were prepared at 5 to 7 Am thickness on glass slides. Laser capture microdissection was done on frozen sections using the Veritas microdissection instrument (Molecular Devices, Sunnyvale, CA) as described in our previous studies (12,13). Whenever possible, adjacent normal mucosal cells directly abutting the aberrant crypts were collected separately by laser capture.…”
Section: Methodsmentioning
confidence: 99%
“…In one study the rate of MSI-H was 89% in adenomas found within 5 cm of a cancer, and 77% of those located > 5 cm from cancer [50] . MSI, of at least one marker, can occasionally be found in ACF [51] , and MSI-L ACF are associated with methylation of MGMT [51] . This lends support to the concept introduced above, that sporadic MSI-L cancers associated with MGMT methylation may represent a unique entity characterized by a common cluster of molecular and pathological events, some of which can be identified even at the earliest stages of carcinogenesis.…”
Section: Microsatellite Instability (Msi) or Mutator Pathwaymentioning
confidence: 99%
“…Given their indisputable relevance to colorectal carcinogenesis, aberrant promoter methylation involving the hMLH1 and MGMT genes might be expected to occur at an early stage in this process (Greenspan et al, 2007;Menigatti et al, 2007), before the gut mucosa exhibits gross changes. Systematic analysis of normal-appearing colorectal mucosa for cancer-relevant DNA methylation changes at these two gene promoters could thus provide insight into the pathological significance of similar changes found in colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%